Research Note: Effect of Light Quality on Fruit Growth, Composition and the Sensory Impact of the Wines - Blancquaert, E. H.; Oberholster, A.; Ricardo-da-Silva, J. M.; Deloire, A. J. Deloire (South African Journal of Enology and Viticulture, 2019)
The stage at which grapes are harvested has an influence on the aromatic and phenolic composition of the berries and the resulting wines. The aim of this study was to evaluate wines harvested sequentially as outlined in the berry sugar accumulation model. Two vintages and treatments in which the light quality and quantity were altered at the fruit zone were compared. In 2010/2011, the grapes were harvested at two ripening stages after the sugar loading plateau was reached, namely the “fresh fruit” stage (20-25 days afterwards) and “pre-mature” stage (at approximately 35 days). In the 2011/2012 season, grapes were harvested 45 days after the sugar loading plateau was reached (the “mature fruit” stage). Vegetative aromas were synonymous with the “fresh fruit” stage in 2010/2011, while the 2011/2012 wines from the “mature fruit” harvest date were characterized by raisin, prune and spicy aromas. In both seasons, the control treatments were rated more intense in ‘satin in the mouth’ in and after expectoration. Wines in which the UV-B radiation was excluded during berry growth were rated the highest in the mouthfeel attribute ‘coarseness’ in both treatment seasons. Wines were analyzed chemically for phenolic content using HPLC, and sensorial using descriptive analysis with a trained panel. In the leaf removal treatments, higher acidity content enhanced the perception of astringency in the wine. Wines were analyzed chemically for phenolic content using HPLC and sensorial using descriptive analysis with a trained panel. Overall, the data showed that grape composition was altered by varying light quality, within a season, but seasonal variation overrode treatment effects. Flavonol concentration in 2011/2012 wine was higher in the exposed leaf removal treatment compared to the other treatments. High light intensities in 2011/2012 season increased anthocyanin concentration in the wine.. This study emphasizes the importance of the quality and quantity of light on the composition and quality of wines, and presents new findings regarding sensory attributes associated with harvesting at different ripening stages.